67-5x=9x+7

Simple and best practice solution for 67-5x=9x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67-5x=9x+7 equation:


Simplifying
67 + -5x = 9x + 7

Reorder the terms:
67 + -5x = 7 + 9x

Solving
67 + -5x = 7 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
67 + -5x + -9x = 7 + 9x + -9x

Combine like terms: -5x + -9x = -14x
67 + -14x = 7 + 9x + -9x

Combine like terms: 9x + -9x = 0
67 + -14x = 7 + 0
67 + -14x = 7

Add '-67' to each side of the equation.
67 + -67 + -14x = 7 + -67

Combine like terms: 67 + -67 = 0
0 + -14x = 7 + -67
-14x = 7 + -67

Combine like terms: 7 + -67 = -60
-14x = -60

Divide each side by '-14'.
x = 4.285714286

Simplifying
x = 4.285714286

See similar equations:

| 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 | | 4x-2=11x-43 | | 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 | | 2x^2-11x-24=0 | | 2(x+3)-3=8-2x | | -21-9x=-32-9x | | 114-3x=24x+18 | | 8-7x=93-42x | | 7,000,000a=10 | | -8b-10=-7-6b | | -2(7w-5)+4w=2(w+2) | | 48x^2=0 | | -4-5x=8-4x | | 81+5y=-4y | | 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) | | 213-4x=32x+21 | | 1/5(3x+12)=3(1-4x)+12 | | -x+4=5x+22 |

Equations solver categories